Rare Earth Elements Variations in a Hyperacid Crater Lake and Their Relations With Changes in Phreatic Activity, Physico-Chemical Parameters, and Chemical Composition: The Case of Poás Volcano (Costa Rica) - Pappaterra, Sabrina; Inguaggiato, Claudio; Rouwet, Dmitri; Mora-Amador, Raúl; Ramírez-Umaña, Carlos; González, Gino; Brusca, Lorenzo; Peiffer, Loic; Levresse, Gilles; Bellomo, Sergio (Frontiers in Earth Science, 2022)
During the unrest phase of 2006-2016 more than 700 phreatic eruptions occurred at the hyperacid and hypersaline crater lake Laguna Caliente of Poás volcano (Costa Rica). In this study, the variation of Rare Earth Elements (REE) dissolved in Laguna Caliente were investigated for the period 2009-2016, when about 679 phreatic eruptions occurred, in order to: 1) scrutinize if they can be used as a new geochemical tool to monitor changes of volcanic activity at hyperacid crater lakes, 2) identify the geochemical processes responsible for the variations of REE concentrations in the lake. The total concentration of REE ranges from 950 µg kg-1 to 2773 µg kg-1, (La/Pr)N-local rock ratios range from 0.93 to 1.35 and Light REE over Heavy REE (LREE/HREE)N-local rock ratios vary from 0.71 to 0.95. REE concentrations, (La/Pr)N-local rock, and (LREE/HREE)N-local rock in lake water vary in relation to the most important changes of volcanic activity and were compared with the variations of major elements and physico-chemical parameters of the lake. Calcium vs. (La/Pr)N-local rock and (LREE/HREE)N-local rock ratios are characterized by different trends when they are compared to the other major elements analyzed (Na, K, Mg, Al, Fe, SO4, Cl). Moreover, higher loss of Ca (up to 2835 ppm) in lake water was found with respect to the loss of Al, K and Na and only the loss of Ca vs. (La/Pr)N-local rock and (LREE/HREE)N-local rock show trends. These results as well as the mass balance calculation simulating the precipitation of gypsum and the removal of REE from lake water, seem to justify the (La/Pr)N-local rock and (LREE/HREE)N-local rock variations recognized in the lake water over time. The observed relation between REE, changes of volcanic activity as well as the parameters commonly used for acid volcanic lakes monitoring (SO4, pH, Mg/Cl), encourages to investigate more profoundly on this research topic in other hyperacid crater lakes to generalize if the REE could be a complementary indicator for changes in volcanic activity.